Behaviour of cold-formed steel lipped channel sections subject to eccentric axial compression. (September 2021) - Peiris, Mithum; Mahendran, Mahen
Abstract: The use of light-gauge steel framed (LSF) wall systems in low- and mid-rise buildings has increased due to the fast and clean construction and robust structural performance. Cold-formed steel studs used as the primary load-bearing component in LSF walls are often subjected to combined axial compression and bending actions caused by loading eccentricity. Research on the effects of loading eccentricity on the compression capacity has been limited while the currently used AS/NZS 4600 and AISI-S100 DSM design guidelines significantly underestimate the load bearing capacities. In this study, 35 lipped channel columns of 0.6 to 1.5 m lengths were tested under concentric and varying levels of eccentric axial compression loading and the resulting load versus axial shortening curves and failure modes were analysed. Non-linear finite element models of tested columns were developed and validated using the test results. Comparison of the ultimate capacities obtained from the tests and finite element analyses against those predicted by the DSM design guidelines showed that the current DSM design guidelines underestimate the capacities whereas a closer agreement was obtained from the improved DSM design guidelines proposed in a recent research study. This paper recommends the improved DSM design method to enable economical and safe designs. Graphical abstract: Unlabelled Image Highlights: Conducted concentric and eccentric axial compression tests of 35 thin-walled and high strength lipped channel sections. Proposed a new test setup using a clamping mechanism for conducting eccentric compression tests of columns. Developed and validated FE models of lipped channel sections subject to large loading eccentricities up to 75 mm. Investigated the accuracy of current and proposed DSM beam-column equations for thin and high strength lipped channels. Demonstrated the benefits of the new DSM for sections buckling in local, distortional, local-distortional and global modes.